Analisis Hukum Multi Akad pada Dana Talangan Haji Bank Muamalat - Muhammad Furqon Almurni; Nuradi Nuradi; Trisiladi Supriyanto (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2022)
Hajj bailout funds have a positive impact as well as a negative impact. One of the negative impacts of haj bailout funds is obscuring the meaning of istitā'ah in the implementation of hajj. This study aims to analyze the multi-contract law contained in the haj bailout contract. The research method of this article is an analytical method based on qualitative data. The author seeks research data on related themes by reviewing articles and conducting interviews with the Muamalat bank unit hajj bailout marketers. From this process, the researcher found that there was a merger of two contracts in the hajj bailout contract, namely the qard contract and also the ijārah contract. One of the important conclusions from this research is that the law of origin of multiple contracts is permissible. However, there is a combination that is forbidden according to the hadith; namely the merger between the qard contract and the sale and purchase agreement. This prohibition also includes the merging of all mu'awwahdāt contracts and qarḍcontracts including ijārah contracts. So the conclusion of this research is the forbidden haj bailout contract; because if there is a merger between the ijarah contract and the debt contract, it becomes a means of usury.